The effect of some irrigation systems and the reduction of mineral fertilizers on soil salinity and the growth and yield of wheat crop - Mousa, Raji Ali; Ulas, Abdullah (Journal of agricultural, environmental and veterinary sciences, 2022)
An experiment was carried out in Iraq, Wasit Governorate, Numaniyah city in 2021 in clay soil with a salinity of more than 4 decimeters- 1, pH 7. To find out the effect of reducing irrigation water and reducing the amount of mineral fertilizer on soil salinity and some growth characteristics and yield of wheat crop.The experiment included On two factors, the first factor included two irrigation systems, namely surface irrigation and sprinkler irrigation, while the second factor included four levels of fertilization p1, p2, p3, p4 in quantities of 200, 250, 350, 450 kg | hectares respectively P4 (450) kg | hectares.The results and statistical analysis showed Show irrigation by spraying r2 and fertilizing p4 at a dose of 450 kg | Hectares outperformed in surface irrigation and lower fertilizer doses in the number of spike grains and the weight of 1000, Grain weight in square meters and harvest index.The experiment was carried out in a splat- plot design with three replicates, and the study included eight treatments in each replicate.
Keywords: Salinity; Sprinkler irrigation; surface irrigation; Fertilizer NPK; Significant; Wheat